Design, dynamic modeling and wave basin verification of a Hybrid Wave–Current Energy Converter. (1st September 2022) - Chen, Shuo; Jiang, Boxi; Li, Xiaofan; Huang, Jianuo; Wu, Xian; Xiong, Qiuchi; Parker, Robert G.; Zuo, Lei
Abstract: Massive and high-density Marine and Hydrokinetic (MHK) energy is contained in the ocean, including waves, tidal streams, and ocean currents. Traditional MHK energy converters harvest energy from only a single MHK energy source, which does not fully exploit the energy potential that co-exists in multiple forms of MHK energy in the ocean. This paper presents the design and dynamics of a Hybrid Wave–Current Energy Converter (HWCEC) that can simultaneously convert both wave and current energy to electricity with a single Power Take-off (PTO) through the engagement and disengagement of the three one-way clutches. The critical design parameters are analyzed through modeling and simulation, including the transmission ratios, the electrical impedance, and the turbine-heave plate distance. Water basin tests in a wave–current tank were conducted, which shows the prototyped HWCEC can improve the electric power output by 38%–71% for regular waves and 79% for irregular waves, while providing a 70% reduction of the Peak to Average Ratio (PAR) of power compared to the baseline Wave Energy Converter (WEC). We further analyze the occurring percentages of the instant power of both WEC and HWCEC in irregular wave tests, shedding new insight on how HWCEC reduces the PAR. Highlights: A Hybrid Wave-Current Energy Converter (HWCEC) with a single Power Take-off (PTO). Dynamic modeling and critical parameter analysis for enhanced power absorption. Water basin tests show power output increased up to 71% in regular waves. Water basin tests show power output increased up to 79% in irregular wave. The Peak to Average Ratio (PAR) is reduced by 70% compared with baseline.